Media framing of childhood obesity: a content analysis of UK newspapers from 1996 to 2014. Issue 4 (4th April 2019) - Nimegeer, Amy; Patterson, Chris; Hilton, Shona
Abstract : Background: Media can influence public and policy-makers' perceptions of causes of, and solutions to, public health issues through selective presentation and framing. Childhood obesity is a health issue with both individual-level and societal-level drivers and solutions, but public opinion and mass media representations of obesity have typically focused on individual-level framings, at the cost of acknowledgement of a need for regulatory action. Objective and setting: To understand the salience and framing of childhood obesity across 19 years of UK national newspaper content. Design and outcome measures: Quantitative content analysis of 757 articles about childhood obesity obtained from six daily and five Sunday newspapers. Articles were coded manually for definitions, drivers and potential solutions. Data were analysed statistically, including analysis of time trends and variations by political alignment of source. Results: The frequency of articles grew from a low of two in 1996 to a peak of 82 in 2008, before declining to 40 in 2010. Individual-level drivers (59.8%) and solutions (36.5%) were mentioned more frequently than societal-level drivers (28.3%) and solutions (28.3%) across the sample, but societal solutions were mentioned more frequently during the final 8 years, coinciding with a marked decline in yearly frequency of articles. Conclusions: Increased focus on societal solutions aligns with public health goals, but coincided with a reduction in the issue's salience in the media. Those advocating public policy solutions to childhood obesity may benefit from seeking to raise the issue's media profile while continuing to promote structural conceptualisations of childhood obesity.